STAT3 Inhibitory Activities of Lignans Isolated from the Stems of Lindera obtusiloba Blume - Eun-Jae Park; Hee Ju Lim; Hyung Jin Lim; Bong-Sik Yun; Soyoung Lee; Seung-Jae Lee; Seung Woong Lee (MDPI AG, 2023)
Lindera obtusiloba Blume has several activities, such as anti-inflammatory, anti-allergic, anti-tumor, anti-wrinkle, and antioxidant activities. Interleukin-6 (IL-6) is a classic pro-inflammatory cytokine that is associated with various functions, such as proliferation, invasion, inflammatory responses and functions within antioxidant defense systems. In this study, we investigated IL-6-induced STAT3 activation of lignan compounds isolated from L. obtusiloba. The structures of the isolated compounds were elucidated via spectroscopic nuclear magnetic resonance (NMR) and electrospray ionization mass spectrometry (ESI-MS). As a result, seven lignans were identified from L. obtusiloba. All the isolated compounds (1-7) were evaluated for their IL-6-induced STAT3 inhibitory effects in Hep3B cells using a luciferase reporter assay. Of the isolates, compounds 1 and 5 showed inhibitory effects against IL-6-stimulated STAT3 activation. Furthermore, the mRNA expression levels of inflammation-related genes such as CRP, IL-1b, and SOCS3 were significantly reduced by exposure to compounds 1 and 5. The protein levels of p-STAT3 and p-JAK2 in IL-6-induced U266 cells were regulated in the presence of lignans derived from Lindera obtusiloba by Western blot assay. Based on the results, this study of L. obtusiloba demonstrates that the species has promise as a bioactive candidate for the treatment of IL-6-induced STAT3-related disease.